A (Des)articulação do Movimento Estudantil: (Décadas de 80 e 90) - Andreza Barbosa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The paper makes an analysis of the student movement on 80's and 90's, having as reference the student movement on 60's and 70's, taking hypothesis about the responsible causes of this movement unarticulation in these years; considering the historical differences among the studied periods. It shows up the uncontrolled political party influences of the movement like one of the principal causes of its unarticulation, or the lack of control of the political party influences, by the students, that have controlled the student movement, stipulating, many times, the directions to be followed and, causing in this way, differences in the form to lead the movement, forgetting the general interests of the students and adopting the party interests.